2019
DOI: 10.1292/jvms.18-0744
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy of laser acupuncture and electroacupuncture in cats undergoing ovariohysterectomy

Abstract: The aim of this study was to compare the effects of laser acupuncture and electroacupuncture on postoperative pain and analgesic requirements in cats. In a prospective, randomized and blinded clinical study, thirty cats undergoing ovariohysterectomy were sedated with intramuscular (IM) ketamine (5 mg/kg), midazolam (0.5 mg/kg), and tramadol (2 mg/ kg). Before the induction of anesthesia, the animals were randomly distributed into three groups of ten cats each: LA: bilateral Stomach 36 (ST-36) and Spleen 6 (SP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…In a full clinical setting using cats, Nascimento et al [ 341 ] studied the effects of an EAP on cats ( n = 10 per treatment group) undergoing ovariohysterectomy (spaying). An electrical stimulator was used to stimulate two acupoints (ST-36 and SP-6), a control group had no EAP treatment, and a third group received infrared laser stimulation of the same acupoints.…”
Section: Resultsmentioning
confidence: 99%
“…In a full clinical setting using cats, Nascimento et al [ 341 ] studied the effects of an EAP on cats ( n = 10 per treatment group) undergoing ovariohysterectomy (spaying). An electrical stimulator was used to stimulate two acupoints (ST-36 and SP-6), a control group had no EAP treatment, and a third group received infrared laser stimulation of the same acupoints.…”
Section: Resultsmentioning
confidence: 99%
“…Even if pain variation over time were not investigated for the VAS, the scale showed very low sensibility and specificity in rabbits. No previous study concerning the VAS in rabbits had been performed previously, however the limitations of the VAS were previously discussed for other veterinary species (8,12,(22)(23)(24). The VAS is a subjective, simple and poorly reliable tool and it is not aimed to consider the multidimensional aspect of pain (25), whereas composite pain scales are objective tools and are intended to capture the behavioral and physiological changes associated with pain.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they are sometimes used in domestic animals (8,12), but their performances have never been previously evaluated in rabbits. Testing a subjective tool like the VAS could be useful to point out the advantages and the limitations of a subjective assessment of pain.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that although LA did not improve the pain scores, it significantly reduced the requirement of rescue medication. To further explore the analgesic effect of LA at SP-6 and ST-36, the same research group [ 60 ] compared the effects of LA and EA on rescue analgesia requirements in cats undergoing ovariohysterectomy. They found that preoperative EA and LA in combination with pain reliever significantly decreased the requirements for rescue analgesia.…”
Section: La On Single Pointmentioning
confidence: 99%